Images and spectral properties of two-component advective flows around black holes: effects of photon bending. Issue 4 (17th November 2016) - Chatterjee, Arka; Chakrabarti, Sandip K.; Ghosh, Himadri
Abstract: Two-component advective flow (TCAF) successfully explains spectral and timing properties of black hole candidates. We study the nature of photon trajectories in the vicinity of a Schwarzschild black hole and incorporate this in predicting images of TCAF with a black hole at the Centre. We also compute the emitted spectra. We employ a Monte Carlo simulation technique to achieve our goal. For accurate prediction of the image and the spectra, null trajectories are generated without constraining the motion to any specific plane. Redshift, bolometric flux and corresponding temperature have been calculated with appropriate relativistic consideration. The CENtrifugal pressure supported BOundary Layer or CENBOL near the inner region of the disc, which acts as the Compton cloud, is appropriately modelled as a thick accretion disc in Schwarzschild geometry for the purpose of imaging and computing spectra. The variations of spectra and image with physical parameters such as the accretion rate ($\dot{m}_{\rm d}$ ) and inclination angle are presented. We show that the gravitational bending effects of photons do change the spectral shape to some extent.